Structural and Electrochemical Characteristics of Graphene Nanosheets as Supercapacitor Electrodes - Ali, Gomaa A. M.; Makhlouf, Salah A.; Chong, Kwok Feng; M. M., Yusoff (Advanced Study Center Co. Ltd., 2015)
In this paper, graphene oxide (GO) was prepared by the Hummers' method and reduced using hydrazine to produce graphene nanosheets (GNS). Physicochemical characterizations of the prepared materials were performed using XRD, FTIR, TGA, DTA, BET, UV-vis, Raman, and FESEM techniques. The results elucidate the structure, morphology, mesoporousity and thermal stability of the prepared samples. Detailed electrochemical studies have been conducted on GNS by CV, galvanostatic and complex impedance measurements indicating some interesting features. GNS shows a specific capacitance of 140 F g-1 at 0.05 A g-1. GNS shows high cyclic stability of about 86% over 1100 cycles at a current density of 1 A g-1. The large electrochemical active surface area suggests that most of the nanosheets are accessible to ions adsorption in the electrolyte system. Impedance spectra show low resistance of GNS, supporting its suitability for supercapacitor electrode applications.